Experimental model for development of intimate hyperplasia - Valiñas, Roberto; Esperón, Alejandro; Keuchkerián, Marcel; Arnoletti, José Pablo; Salom, Andrés; Machado, F; Gateño, M (Cirugía del Uruguay, 1994)
Based on the necessity of practica! experimental models far the obtaining of /esions of intima/ hyperplasia, the authors present their experience at the Departamento de Cirugía Básica (Basic Surgery Dept.) of a model of arterial /esion in dogs by means of arterial dilatation with Foley sound. This was performed in 20 animals which were divided into series according to evolutions of 7, 1 O, and 15 days. Arteries were studied macro and microscopically; lesions of intima/ hyperplasia were obtained in the 15 day evolution series.